(3cJGH aj JGQjN CjGe GdeQMhe GdSjO UGdM HGjs
(3ChdgG (B:s
(3gPG PcQ WQa jSjQ jJYdb HCjGe GeQMhe GdSjO UGdM HGj CYde Cfg dGjNai Ydi GdNGU hGdYGe Cf GdhdGjI GdLRGFQjI cGfJ eJZdHI Ydi CejQ JhfS s
(3BNQgG (B:s
(3hHbi MSjf HGj jMce Ydi MSH eGjXgQ dg hHfi HOGQ GdHGj deMceI hJhdi ecGfg oeUWai HGj GdhRfGLj GfJgi oeNJUQkG hGddg Gdoehab ddUhGH s
(3Vef eLehY , JQJjHgG (B: (3ef U (B208 - (3U(B222s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B337 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQHGW (B((3O (B709) s
Keywords: (3GdJGQjNs